2022
DOI: 10.3390/horticulturae8090770
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Whey Protein Edible Coating Incorporated with Mango Peel Extract on Postharvest Quality, Bioactive Compounds and Shelf Life of Broccoli

Abstract: The present study evaluated the impact of edible coatings based on whey protein concentrate (WPC) and mango peel extract (MPE) on the shelf life, physicochemical, and microbial properties of minimally processed broccoli preserved at 5 ± 1 °C for 28 days. The variations in the physicochemical and microbial properties of the broccoli fresh-cuts were evaluated by determining the following parameter changes: weight loss, color, respiration rate, ascorbic acid content (AsA), sulforaphane content (SF), total phenoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 63 publications
(90 reference statements)
2
5
0
Order By: Relevance
“…Weight loss is the main challenge after harvest because it decreases the appearance and quality of horticultural crops. It has been reported that transpiration and respiration of fresh fruits and vegetables are the main reasons for water loss [29,30]. Our results and previous work indicate that melatonin application retards the loss of water during cold storage [31].…”
Section: Discussionsupporting
confidence: 79%
“…Weight loss is the main challenge after harvest because it decreases the appearance and quality of horticultural crops. It has been reported that transpiration and respiration of fresh fruits and vegetables are the main reasons for water loss [29,30]. Our results and previous work indicate that melatonin application retards the loss of water during cold storage [31].…”
Section: Discussionsupporting
confidence: 79%
“…The values were in the range 32.60-61.70% and 48.40-101.10%, respectively. The remaining drying temperatures (20,30,40, and 70 °C) were characterized by similar values of elongation at break, ranging from 22.60 to 45.00%. Notably, temperatures between 20-60 °C had a significant impact on increasing the elongation of coatings with a 2% jojoba oil content (from 24.3 to 101.1%).…”
Section: Effect Of Drying Conditions and Jojoba Oil On The Mechanical...mentioning
confidence: 99%
“…Their composition also contributes to the enhancement of the nutritional properties of the coated food. Whey proteins have been used in different applications, including fruits such as apples [18] or plums [19] and vegetables such as broccoli [20] as well as in prolonging the shelf life of cheeses [12,21].…”
Section: Introductionmentioning
confidence: 99%
“…An example includes edible coating developed using mango peel extracts and whey protein concentrate to pack broccoli-fresh cuts, leading to lower weight loss and microbial counts than the uncoated broccoli-fresh cuts. 46 Smart films that act as freshness indicators of livestock products such as lamb, can also be developed using fruits and vegetables byproducts such as pomegranate peel powder. 47…”
Section: Extract/juicesmentioning
confidence: 99%
“…Besides whole fruits/pulps, extracts from byproducts such as peels can also be utilized with suitable additives to develop FVBGFs. An example includes edible coating developed using mango peel extracts and whey protein concentrate to pack broccoli‐fresh cuts, leading to lower weight loss and microbial counts than the uncoated broccoli‐fresh cuts 46 …”
Section: Vegetables and Fruits As Sources Of Fvbgfsmentioning
confidence: 99%